CONTEXTUALIZED STRATEGIC INTERVENTION MATERIALS IN GRADE 9 MATHEMATICS - Adonis, Aiko B (PEOPLE: International Journal of Social Sciences, 2020)
This pre-experimental study developed ten (10) Contextualized Strategic Intervention Materials (CSIMs) for the third quarter least mastered Grade 9 Mathematics competencies. The developed CSIMs were based on the generalized least mastered skills of a High School for SY 2015 – 2018. The three (3) least mastered skills were: prove theorems on the different kinds of parallelogram (rectangle, rhombus, square); solve problems involving parallelograms, trapezoids and kites; and solve problems that involve triangle similarity and right triangles. The CSIMs developed addressed the above-cited least mastered skills integrating features of: Bicol culture, use of language learning strategies, and awareness of Disaster Risk Reduction and Management. Students’ significant learning experiences in, and the effect of CSIMs on students’ conceptual understanding were also tackled. Five (5) teachers each for the three features, using DepEd’s LRMDS for SIM, evaluated and rated the CSIMs very evident (at mean 4.73 of 5). Further, the CSIMs under each focus area were evaluated excellent (mean of 4.78 of 5). Students’ significant learning experiences were extracted from the students’ journal entries, teachers’ observation, and Focus Group Discussion responses. The significant learning experiences of Grade 9 students in using the CSIMs were: (a) gained new experiences and developed into independent learners, (b) learned effectively and found the topics easy to understand, (c) became more interested in learning Math topics, (d) appreciated problem solving, and (e) enjoyed and felt comfortable in learning Math topics using the CSIM. Students’ conceptual understanding improved and were significantly different (p < 0.05) for the formative and summative assessments. The set of Contextualized Strategic Intervention Materials (CSIMs) is recommended for: use to promote meaningful learning; further improved by considering other features and subject areas; replication to validate the reliability of the results and expand the learning experiences of students; and collaboration among teachers is encouraged for the development of CSIMs.